Dam Bank Stability in loosely layered silty sands and lean silty sandy clays : Comments on the risk of failure in the North Spur at Muskrat Falls in the Churchill River Valley, Labrador, Newfoundland - Bernander, Stig; Elfgren, Lennart (Luleå tekniska universitet, Byggkonstruktion och brand, 2018)
The differences in landslide analysis between the classic limit equilibrium method (LEM) and a progressive failure procedure is outlined. In LEM the soils are presumed to be fully plastic, whereas in the progressive failure approach the joint effect of strain-softening material properties and deformations in the soil mass are considered. The risk of failure in the North Spur ridge due to the dam impoundment at Muskrat Falls in the Churchill River Valley (Labrador/Newfoundland) is investigated. An important issue in this context is e.g. that sloping failure surfaces near the cut-off wall (COW) are bound to be much more critical than the horizontal failure planes, which have hitherto been considered according to Nalcor/SNC-Lavalin Engineering Reports. Results from progressive failure analyses have now been obtained, applying plausible deformation-softening material properties to the soils in the ridge. These results, which are presented at the end of this report, render unsatisfactory safety factors – i.e. lower than 0.5, thus indicating potential risks of failure when the water surface is raised to the proposed levels. Three reports and a summing up are appended, where Dr Bernander strongly emphasizes the need of stability evaluations based on proper progressive failure analysis – i.e. using soil properties based on tests that are not carried out under fully drained conditions. Measures to reducing the detrimental effects of high in-situ porosity are also proposed.